Clinical symptoms and severity of elderly COVID-19 patients infected with different SARS-CoV-2 variants - Hai-feng WANG; Ya-fei LI; Jing-jing PAN; Aiguo You; RuoLin Wang; Wei Fan; Wenhua Wang; Yingying Wang; Ying Ye; Xueyong Huang; Wanshen Guo (Editorial Office of Chinese Journal of Public Health, 2022)
Objective To analyze differences in clinical symptoms and severity of elderly coronvirus disease 2019 (COVID-19) patients infected with Delta, Omicron BA.1 and Omicron BA.2 variants of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). MethodsFrom China's Infectious Disease Information System, provincial center for disease control and prevention, and local designated hospitals, we collected socio-demographic and clinical information on 60 years and older COVID-19 patients reported in the four large-scale COVID-19 epidemics in Henan province during 2022 and the SARS-CoV-2 variants for the patients' infections were identified based on gene sequencing in combination with epidemi-ological investigation. Chi-square and Fisher's precision probability test were used to compare the differences in the incidence of patients infected with different variants and multivariate logistic regression was adopted analyze the influencing factors of disease severity. ResultsThe total number of elderly cases for the four local COVID-19 epidemics was 234, including 118, 36, and 80 cases infected with SARS-CoV-2 Delta, Omicron BA.1, and Omicron BA.2 variant. Of all the cases, 56.8% were female; 47.6% suffered from underlying diseases; and 88.0% had COVID-19 vaccination. The main clinical manifestations for all the cases were fever, fatigue and upper respiratory symptoms such as cough, sore and dry throat. The symptomatic proportion in the cases with Delta variant infection was significantly higher than that in the cases with Omicron variant infection (34.7% vs. 19.0%, P = 0.007). The proportion of severe or critical conditions was significantly higher in the cases with Delta variant infection than that in the cases with Omicron variant infection (12.7% vs. 1.7%, P = 0.002). The results of multivariate logistic regression analysis revealed following risk factors for the occurrence of severe or critical conditions among the elderly cases: infected with Delta variant (odds ratio [OR] = 5.7, 95% confidence interval [95% CI]: 1.1 - 31.2), aged ≥ 80 years (OR = 8.4, 95% CI = 2.0 - 34.4), suffering from dyskinesia (OR = 5.3, 95% CI: 1.5 - 18.3), and suffering from diabetes (OR = 5.7, 95% CI: 1.1 - 31.3). ConclusionIn COVID-19 patients aged 60 years and above, clinical symptoms and the occurrence of server or critical conditions differ by different SARS-CoV-2 variants and the patients with Delta variant infection, at older age, and with underlying diseases are at a higher risk of having severe or critical conditions.